Insulin Regimens and Clinical Covariates among Type 2 Diabetes patients - Mahmoud Emad El-din Mohamed Abdalla1; Gehan Fathy Attia; Eman Abdalla Mohamed El-Shorbagy; Mona Sami Hamed (Zagazig Journal of Pharmaceutical Sciences)
Background: Different insulin regimens are used to manage poorly controlled diabetic patients. The variability in these regimens leads to differences in patients' experiences and clinical outcomes. Understanding the impact of different insulin regimens on patient outcomes is crucial for optimizing diabetes management. Objective. This study compared insulin experiences and clinical outcomes in outpatient type 2 diabetic patients using two commonly prescribed insulin regimens. Methods. In this comparative cross-sectional study, patients were divided into two groups, each comprising 25 individuals.The study was carried out at Zagazig University Hospital and Al Mabara Health Insurance Hospital in Zagazig, Egypt, for 6 months. The research utilized a validated questionnaire, the Insulin Treatment Experience Questionnaire (ITEQ), to assess patients' experiences with insulin treatment and explore various clinical covariates associated with diabetes in both groups. Results: The findings revealed inadequate glycemic control in both insulin regimen groups, as indicated by elevated levels of glucose indices. Notably, three domains of ITEQ showed significant differences, with higher mean scores observed in the basal-bolus group (p-value < 0.05). A statistically significant positive correlation was found between total ITEQ scores and Insulin Therapy Related-Quality of Life (ITR-QoL) (r=* 0.607* and r= 0.749*, respectively). Conclusion: Patients utilizing basal-bolus insulin analogs exhibited superior glycemic control and quality of life in comparison to individuals employing premixed human insulin.The study emphasize the importance of incorporating patient-reported outcomes into healthcare provider follow-up, providing valuable insights to enhance the overall patient experience of treatment.